If it's not what You are looking for type in the equation solver your own equation and let us solve it.
0.5(6x+12)=2(x+4)
We move all terms to the left:
0.5(6x+12)-(2(x+4))=0
We multiply parentheses
3x-(2(x+4))+6=0
We calculate terms in parentheses: -(2(x+4)), so:We get rid of parentheses
2(x+4)
We multiply parentheses
2x+8
Back to the equation:
-(2x+8)
3x-2x-8+6=0
We add all the numbers together, and all the variables
x-2=0
We move all terms containing x to the left, all other terms to the right
x=2
| a÷6+2=13 | | -6=-z-6z | | 4y+6=62 | | 4x−1/3=2x+4 | | x+3x-5+2x/2=184 | | 120(x+4)+90=1320 | | 2/3(x+1)=1/2 | | 1=-10x-x | | x+3x-5+5x/2=184 | | y+y-6y=9 | | 26x+133=13x+100 | | -9x+x=-3 | | 1.12x-3=0.6-0.2x | | 3(x+1)/2(2x+3)=1 | | -20=-w+5w | | (2x-2)²-(2x-1)²-3(x-4)(x+4)+3x²=3 | | -4g=16 | | .3x-1.5=4.6 | | X+81=2x | | -2-7=8y-y | | X=2x-81 | | 5w+6=25 | | 5m+6=25 | | -2/√3+1=2√3-√3x | | -4=z-3z | | x*99+x=2000 | | x99+x=2000 | | 5/11(x+2)−8=2 | | 5/11(x+2)−8=22 | | 511(x+2)−8=22 | | 4/x-2=7 | | 1+5x=29 |